Floral Richness And Seasonalityof Phytodiversity In The Tessala Mountains, Western Algeria - Saidi, Boubakr; Latreche , Ali; Dif, Mustapha Mahmoud (Bangladesh Journal of Plant Taxonomy, 2023)
This work is devoted for the floral richness and seasonality evaluation of the plant communities of the Tessala Mountains in Western Algeria. The floristic inventory of the 30 surveys carried out on 10 selected stations has resulted in 152 species under 125 genera and 48 families. Seasonal floral richness is concentrated in both spring and summer seasons, while the monthly richness is significant between Marchto August. Vegetations formations are represented physiognomically by four strata, taken into consideration in descending order of importance: Herbaceous (68%), shrubby (12%), arbustive (11%), and arborescent (10%). The overall and seasonal distributions of biological types almost follow the diagrams: Therophytes (The)> Hemicryptophytes (Hem)> Phanerophytes(Pha) > Chamephytes (Cha)> Geophytes (Geo). During the two season: the winter and the spring, the annual herbaceous dominate the bio-morphological spectrum with perennial herbs. During the summer and autumn, perennial herbaceous plants dominate the bio-morphological spectrum. The families that are mostexisting overall and during the four seasons are Asteraceae, Poaceae, Lamiaceae and Fabaceae. Bangladesh J. Plant Taxon. 30(2): 233-248, 2023 (December)